Desenvolvimento de um cronômetro com sensores infravermelhos como plataforma aberta e acessível para experimentos de cinemática com trilhos de ar - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This work presents the development of a low-cost stopwatch based on the Arduino microcontroller platform and infrared sensors, intended for conducting kinematics experiments with air tracks. The objective is to offer an accessible and easily replicable alternative to commercial devices commonly used in teaching laboratories, which are often expensive. The developed system enables precise time measurements in experiments involving Uniform Rectilinear Motion (URM) and, potentially, Uniformly Accelerated Rectilinear Motion (UARM), using four reflective infrared sensors positioned along the track. The collected data is displayed on an LCD screen, requiring no prior programming knowledge from the user. The project follows an open-source approach, allowing for future modifications and enhancements. In addition to detailing the construction process, the work includes the validation of the instrument through a comparison between the data obtained by the stopwatch and a logic analyzer, highlighting the system's limitations and accuracy. The results indicate that the proposal significantly contributes to making experimental activities in Physics Education more accessible, fostering learning through the integration of technology into laboratory practices.
Keywords: Ensino de Física; Automação; Tecnologias Educacionais; Physics Education; Automation; Educational Technologies; CIENCIAS EXATAS E DA TERRA